Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm looking for the power series for $f(x)=\frac{3x^{2}-4x+9}{(x-1)^2(x+3)}$

My approach: the given function is a combination of two problems. first i made some transformations, so the function looks easier.

$$\frac{3x^{2}-4x+9}{(x-1)^2(x+3)})=\frac{3x^{2}-4x+9}{x^3+x^2-5x+3}$$

Now i have two polynomials. i thought the Problem might be even easier, if thinking about the function as:

$$\frac{3x^{2}-4x+9}{x^3+x^2-5x+3)}= (3x^{2}-4x+9)\cdot \frac{1}{(x^3+x^2-5x+3)}$$

Assuming the power series of $3x^{2}-4x+9$ is just $3x^{2}-4x+9$ itself. I hoped, i could find the power series by multiplying the series of the both easier functions.. yeah, i am stuck.

$\sum\limits_{n=0}^{\infty}a_{n}\cdot x^{n}=(3x^{2}-4x+9)\cdot \ ...?... =$ Solution

share|improve this question
    
Have you thought about the fact that (3x^2-4x+9) = (3x^2-4x+1+8) = (3x-1)(x-1)+8 ? –  rbm May 11 '13 at 12:27
    
you mean i should form the Expression this way: $\frac{3x^{2}-4x+9}{(x-1)^2(x+3)}=\frac{(3x-1)(x-1)+8}{x^3+x^2-5x+3}=\frac{2}{(x‌​-1)^2}+\frac{3}{x+1}$ ? –  Toralf Westström May 11 '13 at 12:41

1 Answer 1

up vote 2 down vote accepted

You can use the partial fraction decomposition: $$ \frac{3x^{2}-4x+9}{(x-1)^2(x+3)}= \frac{A}{1-x}+\frac{B}{(1-x)^2}+\frac{C}{1+\frac{1}{3}x} $$ and sum up the series you get, which are known.

If you do the computation, you find $A=0$, $B=2$ and $C=1$, so

$$ \frac{3x^{2}-4x+9}{(x-1)^2(x+3)}= \frac{2}{(1-x)^2}+\frac{1}{1+\frac{1}{3}x} $$

The development of $(1-x)^{-2}$ can be deduced from the fact that $$ \frac{1}{1-x}=\sum_{n\ge0}x^n $$ so, by deriving, we get $$ \frac{1}{(1-x)^2}=\sum_{n\ge1}nx^{n-1}=\sum_{n\ge0}(n+1)x^n $$

The power series for the other term is again easy: $$ \frac{1}{1+\frac{1}{3}x}=\sum_{n\ge0}\frac{(-1)^n}{3^n}x^n $$ so your power series development is

$$ \frac{3x^{2}-4x+9}{(x-1)^2(x+3)}= \sum_{n\ge0}\left(2n+2+\frac{(-1)^n}{3^n}\right)x^n $$

share|improve this answer
    
$\frac{2}{(x‌​-1)^2}+\frac{3}{x+1}$ ? –  Toralf Westström May 11 '13 at 12:57
    
@ToralfWestström No; you have $x+3$ in the denominator of the original fraction. –  egreg May 11 '13 at 13:01
    
but where did you get the $1+\frac{1}{3}x$ from? –  Toralf Westström May 11 '13 at 13:18
    
@ToralfWestström Just observe that $\frac{C}{1+x/3}=\frac{3C}{3+x}$; the form with $1+x/3$ makes it easier to write down the power series. –  egreg May 11 '13 at 13:19
    
i still don't get it. how can i make partial fraction from the given function to this form? –  Toralf Westström May 11 '13 at 13:36

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.